Case of dynamin 2 mutation‐related sporadic centronuclear myopathy with peripheral neuropathy. Issue 4 (29th January 2015) - Kawasaki, Yuko; Naba, Ichiro; Azuma, Shingo; Yaka, Keiko; Moriya, Masayuki; Nakano, Misa; Nishino, Ichizo; Tatsumi, Chikao
Abstract A 53‐year‐old man presented with bilateral ptosis, diffuse muscle weakness and easy fatigability, and was admitted to Toyonaka Municipal Hospital, Osaka, Japan. The patient was diagnosed with myasthenia gravis in his childhood. Since then, he had been developing muscle weakness with atrophy. A nerve conduction study showed motor and sensory neuropathy. Repetitive stimulation of his accessory nerve at 3 Hz showed 30.4% attenuation. We suspected that his symptoms were a result of myasthenia gravis and/or Guillain–Barré syndrome, and started gamma globulin therapy and prednisolone. Because muscle weakness did not respond to our therapy, we carried out muscle biopsy. He was then diagnosed with centronuclear myopathy. Genetic analysis showed the presence of dynamin 2 mutation.